The Self-Recognition of Identity Ashaninka vs Asheninka - Jacinto Santos, Pablo Edwin (2010)
This work is a study on self-recognition of the local identity of the word 'Asháninka' in their sense multifunctional. It analyzes and compares morphologically lexical entry Asháninka vs ashéninka as two groups seeking power that operates as two variants with a similar mega-diversity of motives and ideals real. Although the work of conceptualization differ on these two words, over time has been increasing and improving, we should note that there is no research on the semantic unit in each of the two words. In this regard we are convinced that a study like this, help with a convincing description of the lexical entry when confronted with real-world significance in the world and within this language. It will also be of real importance to those investigating the various achievements of the linguistic phenomenon in the language Asháninka.